Application, innovation, and quality control of endoscopic thyroidectomy by gasless unilateral axillary approach - GUO Yawen, ZHENG Chuanming, GE Minghua (Waike lilun yu shijian)
The endoscopic thyroidectomy by gasless unilateral axillary approach (GUA) represents a significant advancement in the field of endoscopic thyroid surgery, offering notable aesthetic and clinical therapeutic benefits. This paper reviewed the current clinical application, core technological innovations, quality control systems, and future developmental directions of GUA. Research indicated that GUA achieved surgical outcomes comparable to traditional open surgery in the treatment of benign thyroid tumors and thyroid cancer, while substantially enhancing cosmetic results and patient satisfaction. By optimizing the surgical approach design, enhancing cavity construction equipment, and standardizing the operational process, GUA markedly reduced the incidence of postoperative complications, preserved the anterior cervical functional area, and improved patients' postoperative quality of life. Furthermore, multidisciplinary collaboration and thorough pre-operative evaluation were fundamental to surgical success, while intraoperative quality control measures and a comprehensive postoperative follow-up system ensured the safety and efficacy of the procedure. In the future, the integration of robotic technology and advancements in single-site devices are anticipated to enhance the role of GUA in endoscopic thyroid surgery, thereby offering patients more minimally invasive and aesthetically favorable treatment options.